Ombyggnation av ett stall för bundna mjölkkor till boxsystem för rekryteringskvigor - Nilsson, Karin (SLU/Dept. of Animal Environment and Health (until 231231), 2011)
To reconstruct a building is a long-term investment for farmers and it is important that people with different qualifications are involved at an early stage for making the system adapted to the animals as well the animal keeper. Therefore, ethologists who can contribute with their expertise are needed to design the system and get it to function well for the animals.